Study of Employee Satisfaction and Organizational Commitment of Teaching and Non-Teaching Staff - Dash , Sidhya B (International Journal of Psychosocial Rehabilitation, 2019)
Worker fulfillment is a factor in inspiration, maintenance and objective accomplishment in the work environment and duty is a factor that incorporate no abundance remaining task at hand, approaching representative with deference, give acknowledgment and prizes, incidental advantages and positive administration. The motivation behind the research paper is to contemplate the worker fulfillment and authoritative responsibility and to look at the fulfillment level of educating and non-teaching staff and its effect on Commitment. This research paper is clear and experimental in nature and purposive inspecting method is utilized select administration colleges. The examination depends on essential information, which has been gathered through auxiliary poll, filled by educating and non-teaching staff part stake 150 respondents of teaching and non-teaching staff of various colleges (10 management college) of Gwalior has been chosen on irregular testing premise .Percentage technique is utilized for information investigation. As indicated by discoveries of this research paper the worker fulfillment impacts responsibility of teaching and non-educating staff. Variables influencing worker fulfillment and responsibility are rewards, stress, leave, advantages and pay given to the staff by the administration which are critical to improve the inspiration level and representative fulfillment.